Antidepressant-like Properties of fish oil on postpartum depression-like rats model: involvement of serotonergic system - Abdul Aziz, Nurul Uyun; Chiroma, Samaila Musa; Mohd Moklas, Mohamad Aris; Adenan, Mohd Ilham; Ismail, Amin; Baharuldin, Mohamad Taufik Hidayat (Multidisciplinary Digital Publishing Institute, 2020)
Pathophysiology of postpartum depression (PPD) has been associated with many factors, such as neuroendocrine, neuroinflammation and neurotransmitter changes. Fish oil (FO) improves PPD both in humans and animals. However, little is known with regards to its pharmacology on a PPD-like rat model. Hence, the current study aimed at investigating the effects of FO on a PPD-like rat model. Female rats were induced with PPD-like symptoms and then randomly divided into six groups (n = 6) for two experimental protocols. Protocol 1 consisted of PPD-like rats (2 mL distilled water), PPD-like + FO (9 g/kg/d) and PPD-like + Fluoxetine (FLX) (15 mg/kg/d) groups of rats, whereas Protocol 2 consisted of PPD-like rats (2 mL distilled water) + PCPA (p-chlorophenylalanine) 150 mg/kg, PPD-like + FO (9 g/kg/d) + PCPA 150 mg/kg and PPD-like + FLX (15 mg/d) + PCPA 150 mg/kg groups of rats, respectively. All treatments were administered orally for 10 days postpartum, except PCPA, which was given intraperitoneally. Prior to euthanasia, the antidepressant-like effect of the FO was evaluated using the forced swimming test (FST) and open field test (OFT) on day 10 postpartum. Biochemical analysis of serotonin, serotonin metabolite and serotonin turnover from their prefrontal cortex and hippocampus were also measured. The results showed that FO decreased immobility time and increased swimming time significantly, but not climbing time in FST. Further, it also decreased serotonin metabolite and turnover significantly in the hippocampus of the PPD-like rats. In contrast, administration with PCPA reversed all the outcomes. The antidepressant-like effects of FO were found to be similar with that of FLX. Thus, it can be concluded that FO exerts its antidepressant-like effects in PPD-like rats through modulation of serotonergic system.